Plasma Drug Concentration of Propranolol and Genetic Study in Chinese Han Patients With Infantile Haemangioma - Li, Li; Yu, Lu; He, Huan; Wei, Li; Xu, Zigang; Zhao, Libo; Sun, Yujuan; Zhang, Bin; Liu, Yuanxiang; He, Rui; Wang, Xiaoling; Ma, Lin (Frontiers in Pediatrics, 2022)
Background and Purpose This study was conducted to explore the plasma drug concentration of propranolol in Chinese Han patients with infantile haemangioma (IH) and the influencing factors, as well as the relationship among plasma drug concentrations of propranolol, β1-AR mutation and CYP2D6 188C>T, efficacy, and safety. Experimental Approach From January 2018 to April 2019, 140 patients with IH who were admitted to the hospital for oral propranolol and agreed to have their plasma concentration of propranolol tested, including 112 patients with β1-AR and CYP2D6 gene tested. Key Results and Conclusions and Implications The mean peak blood levels of propranolol, 4-hydroxypropranolol (4-OH-P), and N-deisopropylpropranolol (NDP) were 60.35 ± 37.90, 1.90 ± 2.37, and 0.24 ± 0.18 ng/ml, respectively. The mean trough blood levels of propranolol, 4-OH-P, and NDP were 24.98 ± 17.68, 0.45 ± 0.52, and 0.05±0.05 ng/ml, respectively. The higher the dose of propranolol, the higher the plasma concentration of propranolol (p = 0.031). The plasma concentration of propranolol was not related to the treatment efficacy.